Deploying Innovation Capability and Its Relevant Sources as a Key to Success: Insights from Slovenian IT firms - Breznik, Lidija (Naše gospodarstvo/Our economy, 2014)
The paper aims to promote innovation capability as a dominant source of competi- tive advantage. As the deployment of innovation capability can be a question of a firm’s survival, the identification of relevant internal and external sources provides a roadmap for success. Building on qualitative data from six representative IT firms, the results indicate that human and organizational resources are the most relevant internal sources in deploying innovation capability. In addition, customers, suppli- ers, and competitors have been recognized as the most relevant external resources. Despite the strong presumption that innovation capability is a dominant capability, it is not a standalone factor. We find that it is strongly linked and interwoven with ma- nagerial and human resources capability. Our paper makes an empirical contribu- tion and offers important managerial implications.